1999
DOI: 10.1128/aac.43.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Aminoglycoside Therapy for Nosocomial Pneumonia Caused by Gram-Negative Bacteria

Abstract: Nosocomial pneumonia is a notable cause of morbidity and mortality and leads to increases in lengths of hospital stays and institutional expenditures. Aminoglycosides are used to treat patients with these infections, but few data on the doses and schedules required to achieve optimal therapeutic outcomes exist. We analyzed aminoglycoside treatment data for 78 patients with nosocomial pneumonia to determine if optimization of aminoglycoside pharmacodynamic parameters results in a more rapid therapeutic response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
1
10

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(174 citation statements)
references
References 27 publications
4
159
1
10
Order By: Relevance
“…With a C max : MIC ratio of Ն10, the potential for clinical response to aminoglycosides was maximized at more than 88%. Kashuba et al 15 showed that the first time an aminoglycoside was given to patients with nosocomial pneumonia, the probability of resolution of white blood cells and temperature by day 7 was Ն90% when the C max : MIC ratio was Ն10. 15 This means that if patients are dosed appropriately to obtain very high peak drug concentrations, the probability of a good outcome is maximized.…”
Section: Max : Micmentioning
confidence: 98%
“…With a C max : MIC ratio of Ն10, the potential for clinical response to aminoglycosides was maximized at more than 88%. Kashuba et al 15 showed that the first time an aminoglycoside was given to patients with nosocomial pneumonia, the probability of resolution of white blood cells and temperature by day 7 was Ն90% when the C max : MIC ratio was Ն10. 15 This means that if patients are dosed appropriately to obtain very high peak drug concentrations, the probability of a good outcome is maximized.…”
Section: Max : Micmentioning
confidence: 98%
“…In a retrospective study, C max /MIC between 8 and 10 was the major determinant for optimal antibacterial activity and clinical response (Table 1) [39]. Also, target Cmax/MIC ratio achieved in the early therapy increased the probability of a rapid therapeutic response for GNB pneumonia [40]. Because of this PD characteristic and a significant PAE, a single daily administration is the optimal solution to increase aminoglycoside antibacterial activity [24•].…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…Im Gegensatz dazu korreliert die Höhe der ᭤Spitzenspiegel von Aminoglykosiden mit dem klinischen Erfolg [97,137].Außerdem haben Aminoglykoside einen ausgeprägten postantibiotischen Effekt, sodass die Talspiegel ohne Beeinträchtigung der Wirksamkeit unterhalb der MHK liegen können. Die Nephrotoxizität der Aminoglykoside beruht auf einer Aufnahme in Epithelzellen des proximalen Tubulussystems, die bei Serumkonzentrationen von ca.…”
Section: Bolusgabe Oder Dauerapplikationunclassified
“…Obwohl pharmakokinetische Untersuchungen wichtig sind, müssen sie vorsichtig interpretiert werden: Zum einen berücksichtigen viele Spiegelmessungen nicht die heute gebräuchliche Einmalgabe von Aminoglykosiden und den postantibiotischen Effekt, zum anderen spiegeln Gewebekonzentrationen von Ciprofloxacin aufgrund seiner intrazellulären Anreicherung nicht direkt die Wirksamkeit gegen Pseudomonas wider. Die Wirksamkeit von Aminoglykosiden bei gramnegativen Pneumonieerregern ist klinisch belegt [97,137], allerdings treten sie aufgrund der Toxizitätsrisiken zunehmend in den Hintergrund.…”
Section: ᭤ Legionellaantigenunclassified